Four flavonoids from Echinosophora koreensis and their effects on alcohol metabolizing enzymes - Choi, Eun Ju; Kwon, Hak Cheol; Sohn, Young Chang; Nam, Chun Woo; Park, Hyun Bong; Kim, Cheol Young; Yang, Hyun Ok (PHARMACEUTICAL SOC KOREA, 2009)
A new prenylated dihydroflavonol, 3-hydroxy-kenusanone B 1, as well as three other known isoflavanones, sophoronol 2, sophoraisoflavanone A 3 and kenusanone H 4, were isolated from the rhizomes of Echinosophora koreensis. The structures of these compounds were elucidated using spectroscopic analyses that included extensive 2D NMR, optical rotation spectrometry and mass spectrometry. All four flavonoids enhanced the activities of alcohol metabolizing enzymes such as alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) at micromolar concentrations. Sophoronol 2 showed a nine-fold increased activation of alcohol dehydrogenase and aldehyde dehydrogenase than a negative control group at concentrations of 100 mu g/mL and 50 mu g/mL, respectively. This study suggests that prenylated flavonoids have the potential to prevent 'hangovers' after alcohol intake.
Keywords: LUPIN ALKALOIDS; ROOTS; DEHYDROGENASE; FLAVANONES; FLOWERS; NAKAI